Role of Magnetic Resonance Imaging Findings in Adults Presenting with New-Onset Seizures - Naila Tamkeen, Ghazala Wahid, Hadia Gul, Neelum Anwaar, Maria Musammar, Rabeea Ehtesham, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: New-onset seizure can be potential life threatening condition. It raises the suspicion of intracranial abnormality or a primary epilepsy .These are mostly diagnosed and differentiated clinically, however diagnostic imaging has important role in evaluating the cause of seizure . Previously studies done on neuroimaging in seizures have mostly focused on assessment of seizures in children or adults in acute emergency however this study focused on new onset seizures in adults .Magnetic Resonance Imaging (MRI) is readily available in tertiary care hospitals these days and is important diagnostic modality for evaluating the causes of new-onset seizure in adults. Aims and Objectives: The purpose of this study was to discuss the magnetic resonance imaging finding in adult patients presenting with new-onset seizure and if the MRI established the cause for the patient's new onset seizure Methods: This was prospective cross sectional study done in 330 adult patients above age of 18 year who presented with new-onset seizures from May 2020 to April 2021. These patients were referred to Radiology department Hayatabad Medical Complex to evaluate intracranial abnormality and to find out the cause of seizure. MRI brain was performed on 1.5T machine and images were independently reviewed by two consultant Radiologists. The findings were summarized and categorized into a study database. Results: In our study 330 adults presenting with new onset seizures underwent MRI within 48 hours of seizure . The mean age was 47 yrs . MRI determined the cause of new-onset seizure in 139 (42.1%) patients while 191(57.9%) studies were normal.. The most common findings were encephalomalacia with gliosis related to previous trauma ,chronic infarcts and surgery ( 38.1%),primary/metastatic brain tumour (24.4%), infectious encephalitis and meningitis(15.8 %), venous sinus thrombosis (8.6%), while and PRESS(7.2%) and vascular malformation(5.7%) were less common findings, . Patients with focal seizures had a higher proportion of potentially epileptogenic lesions (64.7%) compared with those with seizures of generalized onset (10.8%) or uncertain type (24.6%) Conclusion: This study emphasizes the importance of magnetic resonanace imaging in adults presenting with acute seizures and its usefulness in determining the epileptogenic lesions and helps in planning the treatment strategy. Keywords: Seizures, Magnetic resonance imaging, Intracranial abnormality.